2018
DOI: 10.1038/s41467-018-04704-9
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional human monoclonal neutralizing antibody that targets a unique conserved epitope on influenza HA

Abstract: The high rate of antigenic drift in seasonal influenza viruses necessitates frequent changes in vaccine composition. Recent seasonal H3 vaccines do not protect against swine-origin H3N2 variant (H3N2v) strains that recently have caused severe human infections. Here, we report a human VH1-69 gene-encoded monoclonal antibody (mAb) designated H3v-47 that exhibits potent cross-reactive neutralization activity against human and swine H3N2 viruses that circulated since 1989. The crystal structure and electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 71 publications
4
72
0
Order By: Relevance
“…Preparation of recombinant H7.5 antibodies. H7.5 Fab for crystallization was prepared as previously described (27). In brief, the heavy and light chains of H7.5 were cloned independently into the phCMV3 vector and fused with an N-terminal IgK secretion signal.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of recombinant H7.5 antibodies. H7.5 Fab for crystallization was prepared as previously described (27). In brief, the heavy and light chains of H7.5 were cloned independently into the phCMV3 vector and fused with an N-terminal IgK secretion signal.…”
Section: Methodsmentioning
confidence: 99%
“…A range of antibodies targeting all three influenza A virus surface proteins (HA, NA and matrix protein) have been demonstrated to be effective when used for treatment in animal models including mice, ferrets or primates, with some antibodies entering efficacy evaluation in swine and even humans [1,3,5,31,[33][34][35]. Nevertheless, HA remains the main target protein for antibodies displaying therapeutic efficacy due to the antigen availability on the virus particle surface.…”
Section: Discussionmentioning
confidence: 99%
“…Vestigial esterase domain-binding antibodies were reported to function mainly by blocking viral egress similar to NA inhibitors [89,101]. Recent studies indicated that vestigial esterase domain-binding antibodies also elicit ADCC that may help to protect against viral infection [102]. Bangaru and colleagues found a monoclonal antibody, H3v-47, that not only can neutralize diverse H3N2 viruses and block progeny viruses release, but also induce potent ADCC activity, suggesting that Fc-effector functions are critical for both HA head and stalk targeting antibodies [102].…”
Section: Hi-negative Head-targeting Mabs Can Mediate Robust Adcc Actimentioning
confidence: 99%
“…Recent studies indicated that vestigial esterase domain-binding antibodies also elicit ADCC that may help to protect against viral infection [102]. Bangaru and colleagues found a monoclonal antibody, H3v-47, that not only can neutralize diverse H3N2 viruses and block progeny viruses release, but also induce potent ADCC activity, suggesting that Fc-effector functions are critical for both HA head and stalk targeting antibodies [102]. Interestingly, these researchers found that this multifunctional antibody can recognize a novel epitope that spans the vestigial esterase and receptor-binding subdomains.…”
Section: Hi-negative Head-targeting Mabs Can Mediate Robust Adcc Actimentioning
confidence: 99%